Grundlagen der Oligometastasierung und Stellenwert der Lokaltherapie - Ricke, J.; Guckenberger, M.; Grützmann, Robert (Onkologe, 2020)
A distinction has traditionally been made in oncology between locally limited and systemically metastasized disease stages, in which local therapies pursued a curative or palliative goal. The term oligometastasis describes a vaguely defined intermediate stage in which randomized studies have demonstrated survival benefits of selected patient groups by using local ablative techniques. Currently, oligometastasis is defined by a limited number of metastases and affected organ systems independent of the tumor entity. Classical empirical evidence of the biological aggressiveness of metastasized tumors, such as disease-free interval or response to chemotherapy is not found in current recommendations. The biological background of a limited metastatic capacity is insufficiently understood as is the detection by biomarkers or gene expression profiles in order to be able to make an even more precise patient selection for a local therapeutic approach in addition to an optimal systemic therapy.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Biomarkers; Chemotherapy; Clinical decision making; Quality of life; Radiotherapy